2018
DOI: 10.1002/wcms.1357
|View full text |Cite
|
Sign up to set email alerts
|

Periodic and fragment models based on the local correlation approach

Abstract: A rigorous treatment of dynamical electron correlation in crystalline solids is one of the main challenges in today's materials quantum chemistry and theoretical solid state physics. In this study, we address this problem by using the local correlation approach and exploring a variety of methods, ranging from the full periodic treatment through embedded fragments to finite clusters. Apart from the computational advantages, the direct‐space local representation for the occupied space allows one to partition the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 205 publications
(414 reference statements)
0
43
0
Order By: Relevance
“…For an excellent review of the local wave function correlation methodsf or the condensed-phase systems, see Ref. [13].…”
Section: Local Correlation Methodsmentioning
confidence: 99%
“…For an excellent review of the local wave function correlation methodsf or the condensed-phase systems, see Ref. [13].…”
Section: Local Correlation Methodsmentioning
confidence: 99%
“…Furthermore, Booth, Grüneis, Kresse, and Alavi have demonstrated that the standard hierarchy of quantum chemical methods and in particular the CC ansatz is also valid for solids . For a review on the uses of CC methods in material science, see the review of Zhang and Grüneis, for a discussion on local correlation approaches for solids, see the work of Usvyat, Maschio, and Schütz …”
Section: Algorithmic Approximationsmentioning
confidence: 99%
“…In contrast to multireference methods, single reference coupled cluster theory is in general not suited to treat strong correlation problems. However, coupled cluster theories have successfully been applied to calculate a wide range of materials properties including (i) cohesive energies of (molecular) solids (Rościszewski et al, 1999;Nolan et al, 2009;Schwerdtfeger et al, 2010;Grüneis et al, 2011;Stoll and Doll, 2012;Booth et al, 2013;Yang et al, 2014;, (ii) pressure-temperature phase diagrams (iii) exfoliation energies of layered materials (Hummel et al, 2016;Sansone et al, 2016;Usvyat et al, 2018) (iv) defect formation energies (Grüneis, 2015b), and (v) adsorption and reaction energies of atoms and molecules on surfaces (Voloshina et al, 2011;Usvyat et al, 2012;Boese and Sauer, 2016;Kubas et al, 2016;Tsatsoulis et al, 2017Tsatsoulis et al, , 2018. Furthermore, the equation of motion coupled cluster theories has been implemented to calculate the excited state and single-electron related properties including electronaddition and removal energies in solids (McClain et al, 2017).…”
Section: Introductionmentioning
confidence: 99%